A Cost Effective Material Tracking and Locating Solution for Material Laydown Yard. (2015) - Song, Lingguang; Mohammed, Tanvir; Stayshich, David; Eldin, Neil
Abstract: In industrial construction, each fabricated material item such as a steel piece or a pipe spool is a unique building element. They are typically staged in a large laydown yard before final on-site installation. Manually tracking and locating each particular item in a large laydown yard can be very time consuming, and excessive man hours spent in this process can negatively impact on field installation activity and overall project performance. This study developed a robust and accurate yet cost effective material tracking and locating solution based on mature tracking technologies. The proposed solution features a handheld computer equipped with barcoding and GPS technologies for laydown yard material tracking and fast retrieval in a cost effective manner. The device scans item barcodes when the item is unloaded in the yard and, meanwhile, captures the GPS coordinates along with the item image, and stores these data in a central database. For material retrieval, material lookup through the database provides geographical location and images of an item, and navigation function gets the crew to the item in a shorter duration. To validate the accuracy of GPS and practicality of this solution, various handheld computing devices with built-in GPS functions were tested by comparing their GPS recordings against the true coordinates of selected geological survey benchmarks. The accuracy is measured by the distance between the true coordinates to the device-recorded coordinates using Vincenty's formula. A prototype system consisting of a mobile device and a software module was developed, and the achieved GPS accuracy is within 3 meters. While the proposed solution has the potential to significantly improve material tracking efficiency, its low initial and operating costs and robust performance make it practical to use in a wide range of projects.